Structures of governance in Song Dynasty China, 960-1279 CE - Hartman, Charles 1946- (Cambridge University Press, 2023)
Charles Hartman presents a groundbreaking revisionist history of the political culture of Imperial China as dominated by a struggle between 'technocratic' and 'Confucian' views of governance. His analysis of the workings of Song governance both complements and extends his acclaimed previous work 'The Making of Song Dynasty History'